Eco-Centric Legal Integration for Environmental Monitoring in Nusantara Capital City (NCC) and Putrajaya - Istislam; Anindita Purnama Ningtyas; Mohamad Rifan; Dina Imam Supaat; Amelia Ayu Paramitha (International Journal of Law and Society, 2025)
The urgency of this research lies in the substantive gap between the idealised eco-centric legal framework and the reality of development oversight and land cover monitoring in the Nusantara Capital City (NCC), which still lags behind the integrated model of Putrajaya. Therefore, a comparative analysis is needed to strengthen smart city-based and eco-centric environmental governance. The objective of this research is to produce a comparative legal analysis between Indonesia (NCC) and Malaysia (Putrajaya) regarding the development oversight and land cover monitoring model to strengthen the legal framework and environmental governance of NCC. This study uses a normative-juridical approach through a statute approach and legal comparison by analysing primary, secondary, and tertiary legal materials deductively and comparatively-analogically to assess regulatory coherence, institutional integration, and environmental monitoring architecture. The results show that NCC regulations are normatively aligned with the principles of eco-centric environmental law, but their implementation is weak due to fragmentation of authority, lack of integration of customary law, and ineffective coordination. The digital monitoring system remains fragmented and not yet interoperable, in contrast to Putrajaya, which displays institutional consolidation and integrated predictive monitoring. The study's conclusions confirm that the NCC's eco-centric alignment remains declarative and requires an Eco-centric–Legal Integration Framework encompassing regulatory consolidation, institutional restructuring, integration of AI-based real-time monitoring, and institutionalisation of public participation. The study's limitations lie in the lack of long-term implementation data. These findings have implications for strengthening the NCC's legal design and offer an original, comprehensive eco-centric legal integration model for the Indonesian smart city context.